Leaf gas exchange and yield of three upland rice cultivars - Alvarez, Rita de Cássia Félix; Habermann, Gustavo [UNESP]; Crusciol, Carlos Alexandre Costa [UNESP]; Nascente, Adriano Stephan; Rodrigues, João Domingos [UNESP] (Instituto Agronômico de Campinas, 2015)
Studies of physiological parameters associated with crop performance and growth in different groups of upland rice (Oryza sativa L.) may support plant breeding programs. We evaluated the role of gas exchange rates and dry matter accumulation (DMA) as traits responsible for yields in a traditional (cv. ‘Caiapó’), intermediate (cv. ‘Primavera’) and modern (cv. ‘Maravilha’) upland rice cultivars. Leaf gas exchange rates, DMA, leaf area index (LAI), harvest indexes (HI) and yield components were measured on these genotypes in the field, under sprinkler irrigation. Panicles per m2 and DMA at flowering (FL) and heading, as well as CO2 assimilation rates (A) were similar across these cultivars. The highest yield was found in ‘Primavera’, which may be explained by (i) a two-fold higher HI compared to the other cultivars, (ii) greater rates of DMA during spikelet formation and grain-filling, as well as (iii) a slow natural decrease of A in this cultivar, at the end of the season (between FL and maturation).
Keywords: Oryza sativa; Net photosynthesis; Harvest index; Dry matter accumulation rates; Crop growth rate